The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5539/ibr.v11n2p205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Marketing in Tertiary Education: Empirical Study of Relationship Commitment and Student Loyalty in Hong Kong

Abstract: This study attempts to investigate the applicability of relationship marketing concepts in the private tertiary education industry. With the rapid growth of tertiary education and new academic structure in Hong Kong, it is interesting to investigate the relationship between relationship commitment and student loyalty, and the key determinants of relationship commitment, in a leading private tertiary education institution in Hong Kong. Questionnaires were designed to collect data, and structural equation modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Second, shared value is important in interpersonal and organizational relations of partnership collaboration (Abosag & Lee, 2013;Ahmady, 2012;Morgan & Hunt, 1994). A partner who benefits from a special relationship will maintain the partnership (Ahmady, 2012;Dagger & O'Brien, 2010;Morgan & Hunt, 1994;Wong, Wong, & Leung, 2018). Third, trust one's willingness to rely on others by believing that without supervision, the appointed person can act accordingly to meet the respective party's interest (Morgan & Hunt, 1994).…”
Section: Higher Education Servicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, shared value is important in interpersonal and organizational relations of partnership collaboration (Abosag & Lee, 2013;Ahmady, 2012;Morgan & Hunt, 1994). A partner who benefits from a special relationship will maintain the partnership (Ahmady, 2012;Dagger & O'Brien, 2010;Morgan & Hunt, 1994;Wong, Wong, & Leung, 2018). Third, trust one's willingness to rely on others by believing that without supervision, the appointed person can act accordingly to meet the respective party's interest (Morgan & Hunt, 1994).…”
Section: Higher Education Servicesmentioning
confidence: 99%
“…Shared value is created by redefining productivity in the value chain that focuses on improving internal operations that increase costs, access to inputs, quality, and productivity achieved through environmental improvements, better utilization of resources, investment in employees, supplier capabilities, and other fields (Porter et al, 2012). Shared value has a significant and positive direct effect on trust (Hessling et al, 2018;Korathad & Boonpattarakan, 2017;Wang, 2009;Wong et al, 2018) Hypothesis 3: Shared value has a significant and positive effect on trust. Phelps and Campbell (2011) found that the most influential factors in trust and relationship commitment were relationship benefits, shared value, and communication.…”
Section: Relationship Of Shared Value and Trustmentioning
confidence: 99%
See 3 more Smart Citations